PENERAPAN EVIDENCE BASED NURSING SENAM YOPHYTTA PADA IBU HAMIL TRIMESTER III DENGAN KELETIHAN - Nisrina Puspaningrum (2023)
Pregnancy is a physiological process that is experienced by women starting from the process of fertilization, the development of the fetus in the uterus to the process of giving birth. One of the changes at the end of pregnancy or in the third trimester is the emergence of fatigue. The cause of fatigue in pregnant women is due to the increasing weight of the mother and also the weight of the fetus in the stomach. One of the non-pharmacological therapies to treat nausea and vomiting is yophytta exercise. Purpose: to determine the effect of Yophytta Gymnastics on the Intensity of Fatigue in Third Trimester Pregnant Women. This study used the literature review method with the application of evidence based nursing in nursing care for two patients with fatigue. The instrument used as a measure of nausea and vomiting in pregnant women uses the CFS (Chalder Fatique Scale). Results: There is a decrease in the intensity of fatigue felt by pregnant women in the third trimester after doing yophytta exercises from a CSF score of 24 to a CSF of 14.